Electrochemical impedance study on nanostructured titanium dioxide polyaniline composite prepared by cyclic voltammetry - Binh, Phan Thi; Duyen, Nguyen The (Vietnam Journal of Chemistry, 2015)
In this study, electrochemical impedance of nanostructured titanium dioxide polyaniline composite prepared by cyclic voltammetry was investigated and suggested an equivalent circuit in which 5 elements taken part, such as Rs represents the electrolyte resistance, CCPE represents the constant phase element, CY represents the young’s surface layer impedance, Rf and Cf represent the resistance and capacitance of material film, respectively. The results showed that the more TiO2 takes part in synthesis solution the bigger electrochemical impedance receives the composite, the more cyclic number carried out during synthesis of material the larger Nyquist cirle from which becomes.